Study of the Mechanical Behavior of Dual-Phase Steel Based on Crystal Plasticity Modeling Considering Strain Partitioning - Yongsheng Xu; Wenjiao Dan; Chuang Ren; Tingting Huang; Weigang Zhang (Metals, 2018)
The similar crystal structures of martensite (BCT) and ferrite (BCC) cause difficulty in distinguishing the grain orientations of individual phases in dual-phase (DP) steels. A dislocation-based multiphase mixed hardening model is presented, considering both ferrite and martensite strain partitioning, to describe the texture-dependent mechanical behavior of DP steels more precisely. This model is based on the ideals that (i) the volume fractions of the constituent phases and the corresponding strain partitioning function are obtained through in situ tensile experimentation, and (ii) the grain orientations of ferrite and martensite are assumed to be in accordance with the overall texture. We applied the model to calculate the macroscopic and microscopic mechanical behavior of DP800 steel using a crystal plasticity finite element (CPFE) code. The results show that the calculated stress-strain response and textural evolution are in good agreement with the experimental results. The dislocation evolution indicates that the rapid hardening of ferrite induces a high hardening rate for DP steels early in plastic deformation. In addition, for the grains corresponding to the texture center orientations of DP800, the activity and dislocation density evolutions of the slip systems are studied.